Woodlands, a disappearing landscape - Lindenmayer, David; MacGregor, Christopher (Ecologist) (CSIRO Pub., 2005)
Australia's little known woodlands once covered huge areas of the eastern side of our continent. Woodlands are distinguished from forests by the fact that their canopies do not touch, tree heights are usually lower and they usually have a grassy understorey. They support a fascinating and diverse array of birds, mammals, reptiles, frogs, invertebrates and plants, and have been under massive pressure from grazing and agriculture over the past 200 years. In many cases only small remnant patches of some types of woodland survive. Understanding and appreciating woodlands is an important way forwar.